2022
DOI: 10.3390/ijerph19148503
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin Supplementation in Pre-Pregnancy and Pregnancy among Women—Effects and Influencing Factors in Romania

Abstract: Introduction: The aim of the study was to identify the consumption of vitamin and folic acid supplements before and during pregnancy in a group of post-partum women (Romanian, Hungarian, and Roma) from Mureș County, Romania, and the influence of socio-economic and behavioral factors on the consumption of vitamins. Materials and Methods: This cross-sectional questionnaire-based study included 1278 post-partum women (during the three days of hospitalization for birth), average age 29.5, registered for giving bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…In addition, 66.5% of women reported using pregnancy multivitamins and multimineral formulations, in the form of food supplements. These results align with those of a 2021 Romanian study, which found that 31% of pregnant women did not use any type of supplement during pregnancy [ 37 ]. This is a worrisome finding, as the detrimental effects of folate deficiency during pregnancy have been observed since 1991 [ 38 ].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, 66.5% of women reported using pregnancy multivitamins and multimineral formulations, in the form of food supplements. These results align with those of a 2021 Romanian study, which found that 31% of pregnant women did not use any type of supplement during pregnancy [ 37 ]. This is a worrisome finding, as the detrimental effects of folate deficiency during pregnancy have been observed since 1991 [ 38 ].…”
Section: Discussionsupporting
confidence: 91%
“…In the absence of official national data pertaining to folic acid supplementation in Romania, owing to its over-the-counter availability, a comprehensive study conducted in 2021 analyzed a sample of 1280 pregnant women in Targu Mures. Of these, 70% did not use folic acid supplements prior to conception, and 31% did not use supplements during pregnancy either [43]. The lack of folic acid supplements associated with a low dietary intake of foods containing this nutrient, based on statistical data, should be a cause for concern.…”
Section: Discussionmentioning
confidence: 99%
“…Correcting these risk factors through diet changes, the use of food supplements [46], lifestyle improvements, training medical personnel to identify these risk factors and inform patients and educate them for healthy behavior [47,48] can represent the preamble of alternative strategies for the prevention and treatment of recurrences of urinary infections, in people in good health, in order to limit the use of antibiotics (Figure 1).…”
Section: Discussionmentioning
confidence: 99%